The prognostic value and immune landscape of a cuproptosis-related lncRNA signature in head and neck squamous cell carcinoma - Li, Yao jun; Li, Hai yan; Zhang, Quan; Wei, Sheng li (Frontiers in Genetics, 2022)
Background: Cuproptosis has been recognized as a novel regulatory cell death, which has been confirmed to promote the occurrence and development of tumors. However, it is unclear whether cuproptosis-related lncRNA has an impact on the prognosis of squamous cell carcinoma of the head and neck (HNSCC). Methods: We downloaded 501 HNSCC tumor samples and 44 normal from TCGA database, combined with RNA-seq data, obtained cuproptosis-related lncRNAs by co-expressed analysis. Using univariate Cox regression analysis and LASSO Cox regression, we got prognostic lncRNA associated cuproptosis to construct and validate prognostic signature of HNSCC, analyzed the immune landscape of the signature. Results: The Prognostic Signature is based on 10 cuproptosis-related lncRNAs including AC090587.1, AC004943.2, TTN-AS1, AL162458.1, AC106820.5, AC012313.5, AL132800.1, WDFY3-AS2 and CDKN2A-DT. The results of overall survival, risk score distribution, survival status in the low-risk group were better than those in the high-risk group. In addition, all immune checkpoint genes we involved were significantly different between the two risk groups (p<0.05). TME showed that immune cell infiltration was positively correlated with Eosinophils. M0 and M2 phenotype macrophages, mast cells activated, NK cells activated, and was negatively related with B cells naive, mast cells resting, plasma cells, CD8T cells, T cells follicular helper, T cells regulatory (Tregs). Consensus clustering identified in molecular subtypes of HNSC. More high-risk sample concentrated in Cluster1, which had a higher TIDE score and SNP alternation than Cluster2. Conclusion: Our study elucidated the correlation between cuproptosis-related lncRNA with prognosis and immune landscape of HNSCC, which may provide references for further research on the exploration of mechanism and functions of the prognosis for HNSCC.